2010
DOI: 10.1007/s11751-009-0078-8
|View full text |Cite
|
Sign up to set email alerts
|

A polytrauma patient with an unusual posterior fracture-dislocation of the femoral head: a case report

Abstract: We report a case of a 27-year-old man who was involved in a high-speed car accident. He sustained multiple organ damage including multiple brain petechiae suggesting diffuse axonal damage, aortic dissection, retroperitoneal haematoma and a fracture-dislocation of the right hip with a femoral head fracture and an ipsilateral intertrochanteric fracture. Due to the general condition of the patient, physiological stabilisation was prioritized, and at 2 weeks the fracture-dislocation of the hip was treated with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Osteonecrosis represents a most devastating complication with an incidence range of 6% at an average follow-up of 32 months [ 6 ]. Although various studies [ 1 , 6 – 10 ] report avascular necrosis (AVN) and arthritis incidence from 8 to 25% and 12 to 20%, respectively, with Pipkin's fracture discloations, we attribute early congrous or near congrous reduction, anatomical fixation and early rehabilitation in reducing incidence of AVN and postoperative arthritis, as seen in this case. Radiotherapy and oral indomethacin have both been shown to be of benefit for prophylaxis against heterotopic ossification.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Osteonecrosis represents a most devastating complication with an incidence range of 6% at an average follow-up of 32 months [ 6 ]. Although various studies [ 1 , 6 – 10 ] report avascular necrosis (AVN) and arthritis incidence from 8 to 25% and 12 to 20%, respectively, with Pipkin's fracture discloations, we attribute early congrous or near congrous reduction, anatomical fixation and early rehabilitation in reducing incidence of AVN and postoperative arthritis, as seen in this case. Radiotherapy and oral indomethacin have both been shown to be of benefit for prophylaxis against heterotopic ossification.…”
Section: Discussionmentioning
confidence: 53%
“…A hip fracture dislocation with contralateral femur fracture is a rare combination, but the incidence is fast growing due to the increased road accidents. Femoral head fractures were first described by Birkett and fracture dislocations were first described by Pipkin [ 1 ]. These complex injuries require a prompt multidisciplinary approach and involvement of multiple specialties for successful patient management, but a universal treatment protocol is lacking due to the lack of established studies [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…53 Similar to the contemporary literature, our study revealed strong association between heterotrophic ossification and head-chest injury. 8,15,27,32,54,55 However, the association between the same with the direction of dislocation and the degree of soft tissue injury or intervention was not significant.…”
Section: Complication: Heterotrophic Ossificationmentioning
confidence: 97%